Design Analysis of Sustainable Composite Slab using Profiled Steel Sheeting : A Case Study based on BS 5950-4: 1994 and EN 1994-1-1: 2004 - Faisal Amsyar, Redzuan (EDP Sciences, 2024)
Composite slabs, combining the structural benefits of steel and concrete, are an integral part of modern construction due to their high load-bearing capabilities and efficiency. Steel sheeting provides tensile reinforcement, while the concrete offers compressive strength, contributing to the sustainability and durability of the flooring systems. Recent projects in Malaysia, such as the construction of high-rise Merdeka 118 and PNB Mall have demonstrated the effectiveness of composite slabs in achieving efficient, robust, and environmentally friendly structures. This study basically involves in examining and reassessing the composition of floor slabs using profiled steel from NS BlueScope Lysaght. Technically, this study has amended a manual excel spreadsheet to reassess the design and in-depth analysis of the composite concrete slab using a case study from PNB Mall projects. Through the checking and re evaluation process, several comments and critical discussions have been made, categorized into two subjects: (a) discussions on the formwork/construction stage analysis, and (b) evaluations on the composite (slab) stage analysis. In conclusion, the MegaFloor modelling software is capable of designing and analyzing composite floor slabs when comparing it to the amended excel spreadsheet calculations. The manual design calculations adhere to BS 5950 Part 4, as well as EN 1994-1-1:2004.